Correlation of fractalkine concentrations in serum and synovial fluid with the radiographic severity of knee osteoarthritis. (November 2013) - Zou, Yucong; Li, Yikai; Lu, Lu; Lin, You; Liang, Weiming; Su, Zhiyong; Wang, Xusheng; Yang, Hui; Wang, Jianming; Yu, Chengfu; Huo, Liwei; Ye, Yongliang
Background: Fractalkine has been detected in synovial fluid (SF) from osteoarthritis (OA) patients. This study aims to examine the relation of fractalkine concentrations in serum and SF with the radiographic severity of OA. Methods: Fractalkine concentrations of serum and SF were measured using an enzyme-linked immunosorbent assay method in 223 patients with knee OA and 165 healthy controls. The progression of OA was classified according to the Kellgren–Lawrence grading system. Results: Elevated concentrations of fractalkine in serum were found in knee OA patients compared with healthy controls [all results median (interquartile range) 226.25 (183.19–259.91) vs. 127.42 (99.54–154.98) pg/mL, P < 0.001]. The case group included 71 knee OA patients with grade 2, 98 with grade 3, and 54 with grade 4. Knee OA patients with KL grade 4 had significantly higher fractalkine concentrations in serum and SF compared with those with KL grade 2 and 3 [serum: 247.68 (215.05–278.64) vs. 212.45 (169.19–247.96) pg/mL, P < 0.001, and 247.68 (215.05–278.64) vs. 222.00 (179.80–254.98) pg/mL, P = 0.005, respectively; SF: 94.95 (76.46–106.68) vs. 74.31 (63.64–84.79) pg/mL, P < 0.001, and 94.95 (76.46–106.68) vs. 80.34 (68.84–96.39) pg/mL, P = 0.001, respectively]. Knee OA patients with KL grade 3 showed significantly elevated concentrations of fractalkine in SF compared with those with KL grade 2 [80.34 (68.84–96.39) vs. 74.31 (63.64–84.79) pg/mL, P = 0.004]. Fractalkine concentrations in serum and SF of knee OA patients were both significantly associated with the disease severity evaluated by KL grading criteria ( r = 0.261, P < 0.001 and r = 0.366, P < 0.001, respectively). Conclusion: The fractalkine concentrations in serum and SF may serve as an effective biomarker for the severity of OA.